Missed Opportunities for Sedation and Pain Management at a Level III Neonatal Intensive Care Unit, India - Kothari, Shikha Y.; Dongara, Ashish R.; Nimbalkar, Somashekhar M.; Phatak, Ajay G.; Nimbalkar, Archana S. (Frontiers in Pediatrics, 2016)
Background:Neonates in the neonatal intensive care unit (NICU) undergo a multitude of painful and stressful procedures during the first days of life. Stress from this pain can lead to neurodevelopmental problems that manifest in later childhood and should be prevented. Objective:To determine the number of painful procedures performed per day for each neonate, to verify documentation of painful procedures performed, and to, subsequently, note missed opportunities for providing pain relief to neonates. Methods:We conducted a cross-sectional study at a level III NICUlocated in a rural part of western India. A total of 69 neonates admitted for more than 24 hours were included.Twenty-nine neonates were directly observedfor a total of 24 hours each, and another 40 neonatal records were retrospectively reviewed for the neonate’s first 7 days of admission. All stressful and painful procedures performed on the neonate were recorded.Also recorded were any pharmaceutical pain relief agents or central nervous system depressants administered to the neonate before or at the time of the procedures. Averagenurse: patient ratio was also calculated. Data was analyzed using descriptive statistics. Results: A documentation deficit of 2.2% was observed. The average nurse: patient ratio was 1.53:1. A total of 13711 procedures were recorded, yielding 44.1 (38.1 stressful, 3.8 mildly painful and 2.2 moderately painful) procedures per patient-day. Common stressful procedures were position changing (2501) and temperature recording (2208). Common mildly and moderately painful procedures were heel prick (757) and endotracheal suctioning (526) respectively. Use of pharmacological agents coincided with 33.48% of the procedures. The choice of drug and time of administration were inappropriate, indicating that the pharmacological agents were intended not for pain relief but rather for a coexisting pathology or as sedation from ventilation with no analgesia. Conclusion: Stressful procedures are common in the NICU;mildly and moderately painful procedures fairly common. Almost two-thirds of the times, no pharmaceutical pain relief methods were used, and when administered, the pharmaceutical agentswere seldom intended for pain relief; this implies poor pain management practices and emphasizes the imperative need for educating NICU nurses, residents, fellows and attendings.